Optimal incentives for patent challenges in the pharmaceutical industry - Enrico Böhme; Jonas Severin Frank; Wolfgang Kerber (Philipps-University Marburg, School of Business and Economics, 2017)
Since the patent system relies on private litigation for challenging weak patents, and patent settlements might influence the incentives for challenging patents, the question arises whether the antitrust assessment of patent settlements should also consider their impact on the incentives to challenge potentially invalid patents. Patent settlements in the pharmaceutical industry between originator and generic firms have been scrutinized critically by competition authorities for delaying the market entry of generics and therefore harming consumers. In this paper we present a model that analyzes the tradeoff between limiting the delay of generic entry through patent settlements and giving generic firms more incentives for challenging weak patents of the originator firms. We show that allowing patent settlements with a later market entry of generics than the expected market entry under patent litigation can increase consumer welfare under certain conditions. We introduce a policy parameter for determining the optimal additional period for collusion that would maximize consumer welfare and show that the size of this policy parameter depends on the size of the challenging costs, the intensity of competition, and the duration between the generics' market entry decisions.
Keywords: L10; L40; O34; 330; patent settlements; collusion; patent challenges